Perceived Stress and Suicidal Ideation among the Farmers: A Cross Sectional Study from the Rural Field Practice Area of a Medical College in Karnataka - Anjana R Joshi; Dattatraya D Bant (Indian Association of Preventive and Social Medicine, 2022)
Introduction: Psychological Stress and other mental health problems are highly neglected in Indian farming Community. Changing climatic, weather and environmental conditions affected the growth of crops and yield. This has resulted in various stressful conditions faced by the farmers. The psychological stress leads to tensions in the family relationship, variations in their daily life, and poor operational decisions while farming and even may lead to farm accidents, suicides among them. Objectives: To study the Stress levels perceived by the farmers and the factors determining the stress among them and to study the suicidal ideation among farmers in the previous 6 months. Method: A Community based Cross sectional study was carried out in the villages of Kalghatagi taluk, among 324 marginal & small scale farmers of age group 18-60 years, using pretested semi-structured questionnaire comprising of socio-demographic details, occupational characteristics, perceived stress and the reasons for stress. The 4 item Perceived Stress Scale was used for the assessment of Stress levels. Higher Score indicates high levels of Stress. Results: Among 324 farmers, 69.8% of the farmers were males, majority of them belonged to 50-60 years, and most of them were small scale farmers. The mean perceived score was 6.29+4.38 SD. Majority of the farmers reported crop failure (35%) and debt (37%) as the reasons for stress. The major determinants of stress among farmers were crop failure, debt and family problems. Among 324 farmers 25.3% reported suicidal ideation in the previous 6 months. The Mean stress scores were high among those with suicidal ideation (12.69±1.12 SD). Conclusion: The study shows that stress levels were high among farmers and are related to the failure of crops, inability to pay the debts and other factors. The Mental health problems of the farmers should be addressed at early stages to reduce the burden of farmers' suicides. Primary mental health care should be made available to the rural population.